2013
DOI: 10.1002/aenm.201300566
|View full text |Cite
|
Sign up to set email alerts
|

Application of Redox Non‐Innocent Ligands to Non‐Aqueous Flow Battery Electrolytes

Abstract: It is widely accepted that increasing global energy demand should be met with renewable sources that do not contribute to the accumulation of greenhouse gases. Several abundant sources meeting these criteria, however, including solar and wind energy, are intermittent due to factors such as day/night cycles and weather variations. [ 1 ] This problem is amplifi ed by the poor match between peak/off-peak use of electricity and the generation capability of these renewable sources. Grid-scale strategies to mitigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 35 publications
(29 reference statements)
0
87
0
Order By: Relevance
“…Such a rate performance is comparable to neutral electrolyte (e.g. NaCl)-based aqueous flow cells, 22, 40 and significantly better than most nonaqueous flow cells41…”
mentioning
confidence: 87%
“…Such a rate performance is comparable to neutral electrolyte (e.g. NaCl)-based aqueous flow cells, 22, 40 and significantly better than most nonaqueous flow cells41…”
mentioning
confidence: 87%
“…While the metal center provides the electrochemical activity of [ML n ], the coordinating ligands plays a pivotal role in determining a number of key parameters of the complex, such as the solubility, diffusivity, reversibility, and redox potential of each electron transfer event. Moreover, non-innocent (redox active) ligands may store additional charge thus increasing the intrinsic capacity of the complex [65]. A multi-step redox process with a sufficient potential difference enables the use of the same redox active compound as both the high potential and the low potential compound, which alleviates the concern of cross contamination.…”
Section: Metal-centered Coordination Complexesmentioning
confidence: 99%
“…2− ] were investigated for their potential application in non-aqueous RFBs [65]. It has also been demonstrated that the reduction of [V(mnt) 3 ] 2− adds one electron to the vanadium (IV) center and the oxidation of [V(mnt) 3 ] 2− removes one electron from the (mnt) 2− ligand.…”
Section: Metal-centered Coordination Complexesmentioning
confidence: 99%
“…22 The second group of compounds are ligand-modified ions, which may be dissolved in aqueous or organic solvents. 22,65,178,[180][181][182] For example, additional capacity has been reported from the ligands of a vanadium complex. 180 More complex organic redox compounds can be modified by chemical functionalization to optimize both the redox potential and solubility.…”
Section: Active Materialsmentioning
confidence: 99%
“…22,65,178,[180][181][182] For example, additional capacity has been reported from the ligands of a vanadium complex. 180 More complex organic redox compounds can be modified by chemical functionalization to optimize both the redox potential and solubility. 19,178 Beyond soluble compounds in RFBs, more recently research activity has increased toward solid active material tailored for RFBs.…”
Section: Active Materialsmentioning
confidence: 99%